2017
DOI: 10.1017/pasa.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

Star Scheduling Mode—A New Observing Strategy for Monitoring Weak Southern Radio Sources with the AuScope VLBI Array

Abstract: The International Celestial Reference Frame suffers from significantly less observations in the southern hemisphere compared to the northern one. One reason for this is the historically low number of very long baseline interferometry radio telescopes in the south. The AuScope very long baseline interferometry array with three new telescopes on the Australian continent and an identical antenna in New Zealand were built to address this issue. While the overall number of observations in the south has greatly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…VieVS is used for scheduling Austral sessions about once a month. It should also be mentioned here that VieVS has special scheduling options like the source-based strategy or the star-mode (McCallum et al 2017), and simulations have demonstrated that the performance of VieVS in terms of scheduling is similar to that of SKED (Sun et al 2014).…”
Section: Scheduling and Simulationmentioning
confidence: 93%
“…VieVS is used for scheduling Austral sessions about once a month. It should also be mentioned here that VieVS has special scheduling options like the source-based strategy or the star-mode (McCallum et al 2017), and simulations have demonstrated that the performance of VieVS in terms of scheduling is similar to that of SKED (Sun et al 2014).…”
Section: Scheduling and Simulationmentioning
confidence: 93%
“…Besides this, there is another optional multiplicative factor of the score. It is possible to use a custom sequence of scans to different source groups as used by the STAR scheduling mode (McCallum et al 2017). When using this option, scores from scans to sources to the current target group are multiplied by a factor of 100 otherwise they are divided by a factor of 100.…”
Section: Othermentioning
confidence: 99%
“…2017 ; McCallum et al. 2017 ) from the AuScope array do have a positive impact. The intensive observing program with the AuScope VLBI network was interrupted, due to the upgrade to VGOS-compatible systems.…”
Section: Introductionmentioning
confidence: 98%
“…As emphasised in the latest realisation of the international celestial reference system (ICRS), ICRF3 (Charlot et al 2020), results for the southern hemisphere still clearly lag behind those of the northern sky, though regular as well as special observing campaigns (e.g. Plank et al 2017;McCallum et al 2017) from the AuScope array do have a positive impact. The intensive observing program with the AuScope VLBI network was interrupted, due to the upgrade to VGOS-compatible systems.…”
Section: Introductionmentioning
confidence: 99%